Pengaruh Model Pembelajaran Make a Match terhadap Hasil Belajar Siswa Di Kelas VII SMP Yapis Manokwari - Damopolii, Insar (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2018)
The purpose of the study was to find out different cognitive student achievement used Make a Match and conventional learning model in pollution and destruction environment and the connection with human activity material in class VII SMP Yapis Manokwari. The method used the quasi experimental with nonequivalent control group design. The sample in this research was conducted in class VIII A as experimental class as many as 28 students and class VII B as control class as many as 25 students. The technique sampling used purposive sampling. The data analysis was t-test and significant É= 0,05. The result showed the significant 0,039 < 0,05 and score of experiment class were 69,21 and control class were 56,4. Conclusion, there is a significant difference in the average cognitive student achievement who are taught by Make a Match learning model and the conventional learning model.